(untitled) (Pravaha, 2018)
This article is designed to assess the impact of real effective exchange rate (REER) on economic growth of Nepal. The study uses annual time series data for the period of 1975 to 2015. Engle- Granger residual based test and error correction model have been used to detect the impact of REER on real GDP of Nepal. The explanatory variables used in the study are real effective exchange rate, broad money supply, trade openness and gross fixed capital formation. The results of the study reveal that real effective exchange rate has positive impact on the real GDP of Nepal. Based on the findings, the study concludes that the transmission mechanism of REER through aggregate demand hold in case of Nepal and this result is compatible with the traditional approach to exchange rate. Finally, it is recommended that broad money supply continues to be relevant monetary policy for Nepal. Moreover, Nepal must use the real exchange rate as one of the macroeconomic policies. Pravaha Vol. 24, No. 1, 2018, page: 206-216